Assessment of Knowledge, Attitude and Practice Levels Regarding Anaemia Among Pregnant Women in Putrajaya, Malaysia - Adznam, Siti Nur` Hidayah; Sedek, Razalee; Kasim, Zalifah Mohd (Pakistan Journal of Nutrition, 2018)
Objective: This study aimed to determine knowledge, attitude and practice levels regarding anaemia among pregnant women in Putrajaya. This study was also conducted to identify the associations between knowledge, attitude and practice and socio-demographic and antenatal characteristics. Methodology: A total of 370 pregnant women participated in this study. Socio-demographic information and antenatal characteristics and knowledge, attitude and practice in relation to anaemia were collected using questionnaires. The Sysmex Haematology Analyser was used to measure the Full Blood Count (FBC). Results: The mean age and haemoglobin level of respondents were 30.2±4.2 years of age and 12.1±4.8 g dL–1, respectively. The median for the total knowledge score was 84.2 and the mean score for attitude and practice were 72.4±6.7 and 69.9±13.1, respectively. The subjects’ knowledge score was higher among the group of second trimester (p